Unique thermal behavior of sphingomyelin species with nonhydroxy and 2-hydroxy very-long-chain (C28-C32) PUFAs - Peñalva, Daniel Alejandro (2013)
In rat germ cells and spermatozoa, sphingomyelin (SM) contains molecular species with nonhydroxy (n) and 2-hydroxy (h) very-long-chain polyunsaturated fatty acids (V), the most abundant being SMs with (n- and h-) 28:4n-6, 30:5n-6, and 32:5n-6 as acyl chains. The aim of this study was to gain information about their thermotropic behavior and interactions with other lipids. After isolation from rat testis, multilamellar and giant unilamellar vesicles from these SMs were examined using fluorescent probes. Only n-32:5 SM and h-32:5 SM displayed a gel-liquid transition temperature (Tt ≈ 21?22°C), the rest remaining in the liquid state in the 5°C?45°C range. The degree of order was larger in bilayers of any of the h-V SMs than in those of their chain-matched n-V SMs. Both, but n-V SM relatively more than h-V SM, decreased the Tt of dimyristoylphosphatidylcholine as their proportion increased in binary phosphatidylcholine:SM liposomes. In contrast to the established ability of 16:0 SM to form lateral cholesterol/SM-rich ordered domains in ternary dioleoylphosphatidylcholine:cholesterol:SM bilayers, neither n-V SM nor h-V SM showed a tendency to do so. Thus, these SMs are in the fluid state and are not involved in this type of domains in spermatozoa at physiological temperatures. However, this state could be altered at the very low temperatures at which these gametes are usually preserved.